2019
DOI: 10.1039/c8sc04641g
|View full text |Cite
|
Sign up to set email alerts
|

How to control selectivity in alkane oxidation?

Abstract: The bulk crystal structure of an oxidation catalyst as the most popular descriptor in oxidation catalysis is not solely responsible for catalytic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 93 publications
(89 reference statements)
3
30
0
Order By: Relevance
“…It is known that MnO x -based catalysts form excellent partial and total oxidation catalysts owing to their enhanced reducibility. Examples of Mn-oxide based catalysts used for oxidation reactions include: Mn 2 O 3 for complete oxidation of methane, 61 Mn-oxide–CeO 2 catalysts for formaldehyde oxidation, 66 Spinel CoMn 2 O 4 for toluene oxidation, 67 mesoporous Mn-oxide catalysts for water oxidation, 68 alkane oxidation over Mn-perovskites, 69 CeO 2 -supported Mn-oxide for propane oxidation, 70 In fact, analogous to the CH 4 dissociation pathway over Mn 2 O 5 moiety envisioned in the present study, operando FTIR spectroscopy elsewhere 71 confirmed the formation of Mn–OH surface species by abstraction of hydrogen atoms by nucleophilic oxygen atoms (Mn–O–Mn) from propane during propane oxidation, providing support for the DFT modelling results and chemical insights presented herein.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…It is known that MnO x -based catalysts form excellent partial and total oxidation catalysts owing to their enhanced reducibility. Examples of Mn-oxide based catalysts used for oxidation reactions include: Mn 2 O 3 for complete oxidation of methane, 61 Mn-oxide–CeO 2 catalysts for formaldehyde oxidation, 66 Spinel CoMn 2 O 4 for toluene oxidation, 67 mesoporous Mn-oxide catalysts for water oxidation, 68 alkane oxidation over Mn-perovskites, 69 CeO 2 -supported Mn-oxide for propane oxidation, 70 In fact, analogous to the CH 4 dissociation pathway over Mn 2 O 5 moiety envisioned in the present study, operando FTIR spectroscopy elsewhere 71 confirmed the formation of Mn–OH surface species by abstraction of hydrogen atoms by nucleophilic oxygen atoms (Mn–O–Mn) from propane during propane oxidation, providing support for the DFT modelling results and chemical insights presented herein.…”
Section: Resultsmentioning
confidence: 54%
“…Moreover, according to this correlation between C-H activation barrier and reducibility of the surface metal oxide site, one of the roles of Na-promotion is to increase the reducibility of surface WO x sites, as evidenced by lowering of peak temperature It is known that MnO x based catalysts form excellent partial and total oxidation catalysts owing to their enhanced reducibility. Examples of Mn-oxide based catalysts used for oxidation reactions include: Mn 2 O 3 for complete oxidation of methane,61 Mn-oxide-CeO 2 catalysts for formaldehyde oxidation,66 Spinel CoMn 2 O 4 for toluene oxidation,67 mesoporous Mn-oxide catalysts for water oxidation,68 alkane oxidation over Mn-perovskites,69 CeO 2 -supported Mn-oxide for propane oxidation,70 In fact, analogous to the CH 4 dissociation pathway over Mn 2 O 5 moiety envisioned in the present study, operando FTIR spectroscopy elsewhere71 confirmed the formation of Mn-OH surface species by abstraction of hydrogen atoms by nucleophilic oxygen atoms (Mn-O-Mn) from propane during propane oxidation, providing support for the DFT modelling results and chemical insights presented herein. Recent state-of-the-art understanding regarding the role of Mn-and Na-promoters in Mn 2 O 3 -Na 2 WO 4 /SiO 2 OCM catalysts puts chemical insights provided in the present work in perspective.It was recently shown via experimental CH 4 +O 2 temperature-programmed-surface-reaction of well-defined single site catalysts that Na 2 WO 4 surface sites could effectively and selectively activate CH 4 in absence of any Mn-promoter to form C 2 products, making the role of Mn-promoter unclear 22.…”
mentioning
confidence: 55%
“…Moreover, the O defect increases apparently at the expense of O lattice when the reaction feed streams over the catalyst (Figure 8). The oxygen can undergo hydrogenation through propane and its derivatives creating thus an O OH , also indicated in the difference plots of the valence bands (Figure 10C), when the oxygen is bound to an Mn (Li et al, 2019). In vicinity to this in situ formed hydroxyl group also O defects are created causing thus the increase in surface concentration of O defect species in the feed.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, scaling relations are broken by the occurrence of strain [83][84][85], defects [86], ensemble effects [87], and intended (addition of promoters or additives) or incidental amounts of impurities in the catalyst [88]. These parameters are strongly influenced by catalyst synthesis and are reflected in the impact of morphology or surface composition on the performance of different catalysts with identical bulk structure [89]. The rate of a catalytic reaction is often governed by only a very small amount of highly active sites, so-called high-energy sites, generated, for example, by strain, executed by the interaction of the active site with its "non-innocent" support [84].…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%